Disclosing the Role of Defect‐Engineered Metal–Organic Frameworks in Mixed Matrix Membranes for Efficient CO2 Separation: A Joint Experimental‐Computational Exploration. (8th July 2021) - Lee, Tae Hoon; Ozcan, Aydin; Park, Inho; Fan, Dong; Jang, Jun Kyu; Mileo, Paulo G. M.; Yoo, Seung Yeon; Roh, Ji Soo; Kang, Jun Hyeok; Lee, Byung Kwan; Cho, Young Hoon; Semino, Rocio; et al.
Abstract: Incorporation of defects in metal–organic frameworks (MOFs) offers new opportunities for manipulating their microporosity and functionalities. The so‐called "defect engineering" has great potential to tailor the mass transport properties in MOF/polymer mixed matrix membranes (MMMs) for challenging separation applications, for example, CO2 capture. This study first investigates the impact of MOF defects on the membrane properties of the resultant MOF/polymer MMMs for CO2 separation. Highly porous defect‐engineered UiO‐66 nanoparticles are successfully synthesized and incorporated into a CO2 ‐philic crosslinked poly(ethylene glycol) diacrylate (PEGDA) matrix. A thorough joint experimental/simulation characterization reveals that defect‐engineered UiO‐66/PEGDA MMMs exhibit nearly identical filler–matrix interfacial properties regardless of the defect concentrations of their parental UiO‐66 filler. In addition, non‐equilibrium molecular dynamics simulations in tandem with gas transport studies disclose that the defects in MOFs provide the MMMs with ultrafast transport pathways mainly governed by diffusivity selectivity. Ultimately, MMMs containing the most defective UiO‐66 show the most enhanced CO2 /N2 separation performance—CO2 permeability = 470 Barrer (four times higher than pure PEGDA) and maintains CO2 /N2 selectivity = 41—which overcomes the trade‐off limitation in pure polymers. The results emphasize that defect engineering in MOFs would mark a new milestone for the future development of optimized MMMs. Abstract : The role of defect‐engineered metal–organic frameworks (MOFs) embedded in a polymer matrix toward advanced mixed matrix membranes (MMMs) for CO2 separation is first disclosed. A joint experimental–computational study, especially focusing on filler–matrix interfacial properties, shows that the defect‐engineered MOFs provide an ultrafast CO2 transport highway to the resultant MMM. The developed MMM material displays promising potential for CO2 capture.